(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1915)
A series of Cymric numerals, from 1 to 20, is still in use in various districts of Strathclyde at the present day. Evidence proved that this Cymric system of enumeration was regularly used by the shepherds of Yorkshire, Westmorland, and Cumberland, in telling off their sheep by scores, and that it was also in use, in the same region, among old women when counting the stitches of their knitting. The conclusion generally arrived at was that this was the remains of an ancient British speech, substantially the same as modern Welsh, although differing from that form of Cymric in certain details.